Analisis Karakteristik dan Tingkat Pendapatan Usahatani Jeruk Pamelo Di Kabupaten Pangkep - Marhawati, Marhawati (Universitas Negeri Makassar, 2019)
This study aims to determine the characteristics of Pamelo orange farmers as well as the level of income and efficiency value of Pamelo orange farming in Ma'rang District, Pangkep Regency. The sampling method used was random sampling (random) with a total of 124 farmers. The method of data collection is done by observation, interview and documentation. The data analysis technique used to calculate the income and the efficiency level of the siam farming uses the R/C Ratio analysis tool. The results showed that the Pamelo orange farming was feasible and profitable to be cultivated at all business scales. For a small scale business with an area of less than 0.5 hectares gives 1.99 times the cost of production incurred, a medium scale business with an area of 0.5 hectare to 1 hectare gives an income of 2.05 of the production costs incurred and the scale large businesses with more than one hectare of land give 2.37 of the production costs incurred